Nível de estresse e coping de enfermeiros do setor de clínica cirúrgica de um Hospital Universitário público, em Fortaleza-Ceará - Barros, Paulo Augusto Soares (2016)
Stress is a very common phenomenon among health care professionals, especially in clinical nurses who live 24 hours a day performing direct patient care. Therefore the objective was to identify the level of stress and coping mode (coping) of nurses in a university hospital in Fortaleza. It is a study of cross-sectional, descriptive quantitative approach, performed surgical clinic of the Hospital Walter Cantídio the Federal University of Ceará. The survey was conducted in November / December 2015 and comprised the sample 23 nurses from a pool of 26. Authors such as Guido, Bianchi and Lima were important to substantiate the analysis. Of the subjects, 17 (74%) were female, 14 (60%) were aged 31-40 years old, an age group still quite young. Regarding the time since graduation 10 (44%) had between 1 and 5 years after graduation and had no less than 1 year or more than 16 years after graduation. Of the total, 13 (57%) have more than one job, also 13 (57%) work 31-40 hours per week. As for the shift 13 (56%) have daytime shifts. In relation to the operating time in unit 11 (48%) have 1-10 years of service in the surgical clinic. There are 14 (61%) had a mean stress, 9 (39%) had low stress and no one showed high stress. The coping factor with the highest average among HUWC of Nurses was seven, which is acceptance of responsibility averaging 5.6. The strategy most commonly used to hang out with stressors without the illness was looking at the problem objectively (average of 4.10). From the data obtained, it is important to have collective discussion to personal and institutional awareness to reduce stressors and hence the stress level of these professionals, so that they can develop their professional activities with reasonable quality of working life.